Cooperative assembly synthesis of mesoporous SrTiO3 with enhanced photocatalytic properties. Issue 93 (21st September 2016) - Kayaalp, Buğra E.; Lee, Young Joo; Kornowski, Andreas; Gross, Silvia; D'Arienzo, Massimiliano; Mascotto, Simone
Abstract : The cooperative assembly of silica precursors and organic metal complexes leads to the synthesis of mesoporous, crystalline SrTiO3 with improved photocatalytic activity. Abstract : The synthesis of mesoporous SrTiO3 by using the cooperative assembly of metal chelate complexes and alkoxysilanes is here presented. The high affinity and intimate mixing between the two precursors fostered the formation, via polycondensation, of interpentrating organic and inorganic polymers. Hence, after calcination and removal of the siliceous phase, aggregates of mesoporous, polycrystalline SrTiO3 with interconnected pores of ca. 10 nm and surface areas as high as 240 m 2 g −1 were obtained. Systems using different SrTiO3  : SiO2 molar ratios were prepared to vary the porosity and microstructure. The templating action of the silica and its effect on the physicochemical properties of the final porous materials were addressed by a multi-technique approach. Finally, the activity of the bulk mesoporous SrTiO3 systems was exemplarily demonstrated by photodegradation tests of methylene blue under UV light. The dye conversion progressively increased with the content of silica template, proving the higher activity of the proposed mesoporous materials.